Self-Disclosure: Hidden Talent Remaja di TikTok - Moekahar, Fatmawati; Hastuti, Retno Astari (Koneksi, 2022)
This study aims to explore the experiences self-disclosure of youth in TikTok social media. This social media has a variety of interesting features and is also a medium to channel one's creativity, express oneself and develop new talents that were previously unknown or not owned, thus enabling the disclosure of hidden talents. In this digital era, many talents are increasingly visible coming from youth. Teenagers who tend to close themselves use social media to reveal themselves through their hidden talents. This study uses a qualitative method, a phenomenological approach with data collection techniques in-depth interviews, observation, and documentation. Informants are three people as users active TikTok from Pekanbaru City. Informants are teenagers who have hidden talents, using TikTok as a means of self-disclosure. The results showed that self-disclosure of hidden talent informants in TikTok media consisted of three meanings: (1) self-existence, (2) satisfaction & happiness, and (3) spent time. Three meanings are interrelated and become an inseparable part. Informants interpret TikTok as a medium to channel hidden talent so that it can continue to exist. The third hidden talent of the informants is as a Beauty of Content Creator. The informant's self-existence gives a sense of satisfaction and happiness because it has received many likes and positive comments, as well as additional income through content affiliated with Shopee Affiliate and live TikTok. The meaning of spent time for informants as an activity with social media which is considered to have positive value because it can channel the hidden talents. The three meanings are self-disclosure hidden talent informants are about feelings, ideas, hopes, and information that is deliberately shared to public using by TikTok media. Penelitian ini bertujuan untuk mengeksplor pengalaman remaja dalam melakukan pengungkapan diri (self disclosure) melalui media sosial TikTok. Media sosial ini memiliki berbagai macam fitur menarik dan juga menjadi media untuk menyalurkan kreativitas diri, mengekspresikan diri dan mengembangkan talenta baru yang sebelumnya tidak diketahui atau tidak dimiliki sehingga memungkinkan terjadinya pengungkapan hidden talent. Di era digital ini banyak talent yang semakin terlihat yang berasal dari para remaja. Beberapa remaja yang memiliki kecenderungan menutup diri menggunakan media sosial sebagai sarana untuk mengungkapkan diri melalui talent tersembunyi yang dimilikinya. Penelitian ini menggunakan metode kualitatif, pendekatan fenomenologi dengan teknik pengumpulan data wawancara mendalam, observasi, dan dokumentasi.  Informan penelitian adalah 3 orang pengguna TikTok aktif yang berasal dari Kota Pekanbaru. Informan adalah remaja yang memiliki talent tersembunyi, menggunakan TikTok sebagai sarana self disclosure. Hasil penelitian menunjukkan bahwa self disclosure terhadap hidden talent informan di media Tiktok terdiri atas 3 makna, yakni makna eksistensi diri, makna kepuasan&kebahagiaan, dan makna menghabiskan waktu luang. Ketiga makna tersebut saling terkait dan menjadi bagian yang tak terpisahkan. Informan memaknai TikTok sebagai media untuk menyalurkan hidden talent sehingga dapat terus eksis. Hiddent Talent ketiga informan adalah sebagai Content Creator of Beauty. Eksistensi diri informan memberikan rasa kepuasan dan kebahagian karena telah mendapatkan jumlah like banyak dan koment positif, serta tambahan penghasilan melalui konten yang terafiliasi dengan Shopee Affiliate dan live TikTok. Makna menghabiskan waktu bagi informan sebagai aktivitas bermedia sosial yang dianggap memiliki nilai positif karena mampu menyalurkan bakat terpendam informan. Ketiga makna tersebut adalah self disclosure hiddent talent informan adalah tentang perasaan, ide, harapan, dan informasi yang sengaja dibagi kepada public melalui media TikTok.